2002
DOI: 10.1177/0145445502026001004
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Behavioral Treatment at School for 4- to 7-Year-Old Children with Autism

Abstract: This study was designed to evaluate 1 year of intensive treatment for 4- to 7-year-old children with autism. An independent clinician assigned children to either behavioral treatment (n = 13) or eclectic treatment (n = 12). Assignment was based on availability of personnel to supervise treatment and was not influenced by child characteristics or family preference. The two treatment groups received similar amounts of treatment (M = 28.52 hours per week at the child's school). Children in the behavioral treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
282
0
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(329 citation statements)
references
References 21 publications
17
282
0
13
Order By: Relevance
“…Howard, Sparkman, Cohen, Green and Stanislaw (2005) maintain that effective early intervention can produce lasting neurobiological as well as behavioral changes as early experiences play a critical role in shaping brain architecture as well as brain function. Research has indicated in numerous studies that early intensive behavioral intervention is highly effective and much more so than an "eclectic" approach (Remington, Hastings, Kovshoff, Espinosa & Jahr, 2007;Zachor, BenItzchak, Rabinovich & Lahat, 2007;Eikeseth, Smith, Jahr & Eldevik, 2002;Howard et al, 2005). Matson and Smith (2008) maintain that to date enough behaviorally oriented EIBI studies have been conducted to suggest that not only is it effective but as a congregate group of learning based methods, it stands alone as the only effective treatment for young children with ASD.…”
Section: Risk Factors For Challenging Behavior 16mentioning
confidence: 99%
“…Howard, Sparkman, Cohen, Green and Stanislaw (2005) maintain that effective early intervention can produce lasting neurobiological as well as behavioral changes as early experiences play a critical role in shaping brain architecture as well as brain function. Research has indicated in numerous studies that early intensive behavioral intervention is highly effective and much more so than an "eclectic" approach (Remington, Hastings, Kovshoff, Espinosa & Jahr, 2007;Zachor, BenItzchak, Rabinovich & Lahat, 2007;Eikeseth, Smith, Jahr & Eldevik, 2002;Howard et al, 2005). Matson and Smith (2008) maintain that to date enough behaviorally oriented EIBI studies have been conducted to suggest that not only is it effective but as a congregate group of learning based methods, it stands alone as the only effective treatment for young children with ASD.…”
Section: Risk Factors For Challenging Behavior 16mentioning
confidence: 99%
“…Children are taught skills including attention, basic discrimination, language and communication, daily living, socialization, play, fine and gross motor control and pre-academics. ABA is also implemented in relatively unstructured situations, using incidental teaching techniques, to enhance generalization, increase motivation, and to develop social skills (Bondy & Frost, 1994;Eikeseth, Smith, Jahr, & Eldevik, 2002;Harris, Handleman, Gordon, Kristoff, & Fuentes, 1991; Koegel & Koegel, 1995;Strain, Kohler, & Goldstein, 1996;Thorp, Stahmer, & Schreibman, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies had a control group, used standardized tests and had reliable outcome measures (reviewed in Kasari, 2002). Most of the studies compared behavioral treatment programs to interventions such as ''eclectic'' programs (Eikeseth et al, 2002;Howard et al, 2005), school based intervention (Sheinkopf & Siegel, 1998), parent training (Smith, Groen, & Wynn, 2000), non-specified interventions (Birnbrauer & Leach, 1993) and no treatment (Lovaas, 1987). Most studies reported behavioral intervention to be a more effective treatment approach (Birnbrauer & Leach, 1993;Eikeseth et al, 2002;Howard et al, 2005;Lovaas, 1987;Sheinkopf & Siegel, 1998;Smith et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We know relatively little about generalization and maintenance of the effects of comprehensive programs, though single-subject designs have increasingly included measurement of these aspects of change (Goldstein, 2002;McConnell, 2002). More recently, some studies of comprehensive behavioral interventions have discussed short-term changes as well as more general outcomes (Eikeseth, Smith, Jahr, & Eldevik, 2002).…”
Section: What Are Unique Issues In Considering the Psychosocial Treatmentioning
confidence: 99%
“…Families must perceive all treatment options as approaches that are strongly recommended by the investigators. It is difficult to keep families in a treatment-as-usual group and impossible to separate the effects of hope, enthusiasm, confidence and often training of the interveners from specific aspects of the treatment (see Eikeseth, Smith, Jahr & Eldevik, 2002), if deliberate plans are not made to take these factors into account.…”
Section: Recruitmentmentioning
confidence: 99%